The water sustainability index in a watershed of the eastern Amazon: an analysis of environmental, hydrological, social, and sectoral use dimensions - Silva Junior, Renato Oliveira; Junior, Wilson Nascimento; Melo, Adayana Maria Queiroz; Almeida, Helena Pereira; Silva, Marcio Sousa; Oliveira, Francisco Souza; Lima, Aline Maria Meiguins De (Frontiers in Environmental Science, 2025)
In this study, we evaluate the water sustainability of the Itacaiúnas River watershed (IRW) in the eastern Amazon using an adapted water sustainability index (WSI). This basin stands out for its intense mineral and agricultural activities across its extent. The index was adapted from the methodology proposed by Chavez and Alipaz (2007), which uses a weighted average to combine different indicators, with weights defined based on the coefficient of variation of the indicators that make up the WSI. This study’s approach integrates the environmental (E) dimension, represented by forest fragmentation; the hydrological (H) dimension, associated with hydrological variability; the social (S) dimension, related to the social progress index; and the public policy (PP) dimension, which considers the pressure from the user sectors. The calculated WSI was 0.37, indicating low water sustainability, which reflected deforestation, forest fragmentation, hydrological variability, and social disparities among the municipalities that comprise the IRW. The environmental dimension demonstrated an increase in forest fragmentation in the territory between 2008 and 2022. The hydrological analysis revealed low water availability during dry periods, which was associated with climatic seasonality, insufficient hydrometeorological data, and climate change. In the social dimension, mining municipalities had the most significant social indicator, but the economic benefit of the activity did not extend to all municipalities in the basin. The public policy dimension indicated high demand, mainly for mining, agriculture, and human supply. The results highlight the need for strategic actions, such as expanding hydrological monitoring, environmental restoration, and strengthening water resource management.